ID 323 – Shortening of the cutaneous silent period duration in tibialis anterior after fatiguing eccentric exercise. Issue 3 (March 2016) - Banea, O.C.; Casanova-Molla, J.; Morales, M.; Cabib, C.; Arca, R.; Brum, M.; Valls-Solé, J.
Abstract : Objective: Muscle afferent feedback (presumably mainly of spindle origin) contributes to the maintenance of alpha motoneuron firing during sustained muscle contraction. We aimed at investigating how a unilateral fatiguing eccentric exercise involving the tibialis anterior (TA) affects inhibitory control of muscle activity. Methods: In 8 healthy subjects, we assessed the TA silent period (SP) to cortical magnetic stimuli (round coil) and to cutaneous nerve electrical stimulation (superficial peroneal nerve at the ankle) before and after 5 min of eccentric exercise. Results: At baseline, SP duration was variable among subjects but cortical SP was always longer than cutaneous SP (111.6 ± 13.8 ms vs. 37.3 ± 10.2 ms). After exercise, there was a slight increase in background EMG activity. The cutaneous SP shortened significantly (24.3 ± 7.3 ms) at the expenses of onset latency delay (98.7 ± 14.0 ms in baseline to 112.2 ± 11.9 ms after exercise). There were no significant changes in cortical SP after exercise (106.2 ± 18.1 ms). Conclusions: Eccentric exercise leads to a delay in onset latency of the cutaneous SP with no changes in cortical SP. An effect of fatigue on small nerve fibers, which are known to contribute to the onset of cutaneous SP, may partly explain our results.